Investigating predictors of fidelity of implementation for a preschool vocabulary and language curriculum. Issue 3 (3rd April 2017) - Phillips, Beth M.; Ingrole, Smriti A.; Burris, Pamela W.; Tabulda, Galiya
ABSTRACT: This study describes initial development, feasibility, and fidelity of implementation of a vocabulary and language curriculum supplement that combined explicit instruction and educational television programming to enhance children's vocabulary acquisition. Efficacy of an intervention relies in part on its fidelity of implementation, but little is known regarding predictors of fidelity itself; therefore, the current study evaluated quality of implementation and its association with teacher characteristics. The implementation of teachers in 39 preschool classrooms was observed for teachers' adherence, and the quality of lesson enactment during 16 weeks of daily lessons. Teachers' preparedness and classroom management significantly predicted teachers' observed and rated implementation quality. Whereas teacher education was not a significant predictor of either metric of implementation quality, teachers' receptivity, and consistency in implementation predicted their rated and observed implementation quality, respectively. Results demonstrate that teachers from diverse educational backgrounds and settings can successfully implement high-quality language-focused instruction.